The relationship among the somatic characteristics, age and covered distance of football players - Soroka, A.; Bergeir, J. (Human Movement, 2011)
The aim of this article was to define the somatic characteristics, BMI index, age and total distance covered of football players who participated in the 2008 European Football Championships. The article also pointed to any significant interrelationships. Methods. On the basis of a game analysis system, the Castrol Performance Index, the 248 football players who participated in all 32 games of the Championships were subject to analysis based on the distance covered during the games, with the results statistically analyzed and compared with the players` somatic characteristics. In addition, the Kruskal-Wallis test was used as a non-parametric counterpart of one-way analysis of variance. Results. The highest values of the somatic characteristics such as height, body mass, age and the BMI index were found in goalkeepers. The longest distances covered during the games were attained by midfielders and side midfielders, whereas the shortest distances covered were by goalkeepers and central defenders. Larger values of height and body mass corresponded to smaller covered distances by players during the games. Conclusions. The indicated dependences, which were found among the players` age, height, body mass and covered distance during the games allows one to define the usefulness of a player in a particular team formation. The covered distance, particularly in correlation with the mentioned morphological indicators, which to a great extent are genetically conditioned, could be used as criterion towards specifying in the most accurate way which formation a particular player should play in, based on his genetic predisposition.